Does Emancipation Matter? Fertility of Chinese International Migrants to the United States and Nonmigrants during China’s One-child Policy Period - Nie, Wanli; Baizan, Pau (The International migration review, 2021)
This article investigates the impact of international migration to the United States on the level and timing of Chinese migrants’ fertility. We compare Chinese women who did not leave the country (non-migrants) and were subject to restrictive family policies from 1974 to 2015 to those who moved to the United States (migrants) and were, thus, “emancipated” from these policies. We theoretically develop and empirically test the emancipation hypothesis that migrants should have a higher fertility than non-migrants, as well as an earlier timing of childbearing. This emancipation effect is hypothesized to decline across birth cohorts. We use data from the 2000 US census, the 2005 American Community Survey, the 2000 Chinese census, and the 2005 Chinese 1 percent Population Survey and discrete-time event history models to analyze first, second, and third births, and migration as joint processes, to account for selection effects. The results show that Chinese migrants to the United States had substantially higher childbearing probabilities after migration, compared with non-migrants in China, especially for second and third births. Moreover, our analyses indicate that the migration process is selective of migrants with lower fertility. Overall, the results show how international migration from China to the United States can lead to an increase in migrant women’s fertility, accounting for disruption, adaptation, and selection effects. The rapidly increased fertility after migration from China to the United States might have implications on other migration contexts where fertility in the origin country is dropping rapidly while that in the destination country is relatively stable.